EVALUATION OF HYPERINSULINEMIA, INFLAMMATION AND LIPID PROFILE IN PATIENTS WITH ENDOMETRIAL CANCER - DR. G.S.R.KEDARI, (International Journal of Pharma and Bio Sciences, 2014)
Endometrial cancer is the most common gynecologic cancer in developed countries and with increasing prevalence in developing countries like India. It has been hypothesized that free circulating insulin levels, Inflammation and altered lipid profile may contribute in the pathogenesis of endometrial cancer. The aim of our present study is to evaluate the role of Insulin, CRP and lipid profile in endometrial cancer. We tried to assess Insulin, Insulin resistance, CRP Levels by CLIA, Homa Index and latex agglutination method respectively. Glucose, total cholesterol and Triacylglycerol were estimated by enzymatic methods with the help of autoanalyser. HDL was measured with the help of divalent cation precipitation method.LDL was calculated by using a standard formula. For this, we have taken 25 cases of endometrial cancer cases and compared with 25 normal women who acted as controls.A significant increase in the levels of free circulating insulin, insulin resistance, CRP and triglyceride levels were observed in cases when compared with controls. A significant decrease in the levels of HDL was observed in cases when compared with controls. There were no significant differences in the levels of LDLand total cholesterol.This suggests that hyperinsulinemia, chronic inflammation and altered lipid profile may play a role in development of endometrial cancer.